To Write or not to Write : Notes on the Poetic Imagination, and the Desire for the Void - Andersson, Lars Gustaf (6th International Conference on Creative Writing, Kozani, Greece, 2024-09-05 - 2024-09-08, 2025)
The paper is a keynote talk, introducing the problem with texts that are not finished - or maybe not even written at all but - but still haunts the imagination of the writer, specifically the creative writing student.
Keywords: Poetic imagination; creative writing; unfinished texts